The Cerita Kita Website: Enhancing Elementary Students’ Multiliteracy and Literary Appreciation through a Local Wisdom-Based Ecocriticism Approach - Mellyaning Khoiriya, Rika; Mudiono, Alif; Yuriananta, Renda; Kurnia, Vika Cahya; Faiza, Afidatun; Azizah, Maulidatil (Universitas Islam Lamongan, 2025)
This study developed the